MODEL PEMBELAJARAN MOVING PEER TUTORING UNTUK MENINGKATKAN LITERASI INFORMASI MAHASISWA - Muhammad Fahmi Johan Syah; Suranto Suranto; Agnia Khulqi Karima; Diah Ayu Widyasari (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2021)
This study aims to test the implementation of moving peer tutoring method to improve information literacy competence of prospective accounting educator students. This type of research is quantitative with an experimental design. This method is implemented on twenty five people as participants and three people as peer tutors who provide information to each other. The pre-test and post-test data were collected through a questionnaire. The instrument reliability test was carried out through validity and reliability tests with 23 respondents being tested. The results of this study indicate that the implementation of moving peer tutoring method is able to improve information literacy competence of prospective accounting educators. A significant increase shows that students in higher education are still comfortable with their learning style with their peers who are relatively the same age. These results need to be re-examined in elementary and middle school students to obtain broader results.